Linguistic Typology at the Crossroads - Caterina Mauri; Nicola Grandi; Francesca Di Garbo; Andrea Sansò (Linguistic Typology at the Crossroads, 2021)
Welcome to Linguistic Typology at the Crossroads (LTC), a new journal dedicated to the crossroads where linguistic typology meets its neighboring fields. A crossroads is not only and necessarily a place where a choice must be made: this is the point of view of the traveler, wondering which way to go. If we take a bird’s-eye view and observe the crossroads from above, we see much more than choices. A Crossroads is the place where different directions, and different travelers, meet or follow each other. Thanks to the crossroads, it is possible to change and exchange, and the very concept of ‘step forward’ opens itself to diagonals and curves. The crossroads is where future is imagined and innovation occurs, thanks to the reciprocal influence of intersecting perspectives. Crossroads means meeting, exchanging, converging, choosing, diverging, changing, and possibly making the difference. This journal aims to take the point of view of the crossroads, capturing the moment when linguistic typology intersects other fields, changing and exchanging methods, theories and data, in the belief that a closer look at the crossroads may reveal converging paths and new directions to go.